Influencer Politics : At the Intersection of Personal, Political, and Promotional - Arnesson, Johanna; Borchers, Nils S.; Domina, Oksana; Ekman, Mattias; Eriksson Krutrök, Moa; Grandien, Christina; Grønli, Tor-Morten; Hogsnes, Mathilde; Laaksonen, Salla-Maaria; Lykke Nielsen, Mette; Pelevina, Nuppu; Pöyry, Essi; et al. (2024)
Influencer Politics focuses on current discussions about the role and impact of social media influencers in the political sphere, and how the personal, political and promotional often converges in digital media. A key question is how core ideas of influencer culture - authenticity, intimacy, commercialism, and self-branding - shape the ways in which politics are expressed and understood in this context, as well as opens up space for new ways of connecting and interacting with the public. It also highlights the way that influencer culture itself is infused with politics, where issues of, for example, empowerment and exploitation are articulated and discussed in different ways. The book is the result of a common interest among researchers engaged in work on political aspects of influencer marketing and influencer culture from critical, cultural, and strategic perspectives, and offers a range of case studies devoted to both the promises and limitations of influencer politics.